Estimation and Prediction of Construction Building Cost Index for Jordanian Construction Industry - Muala, Ahmad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2020)
Construction Cost Index is an indicator of the average cost movement over time of particular goods and services that represent the construction industry. The main purpose of Construction price indicators is to estimate the degree of price variations of either the inputs, or outputs, of construction activity. Nevertheless, the nomenclature used mainly depends on the context of indices and can vary between countries. At the same time, every individual construction project is a mixture of a specific collection of structural elements, mechanical elements, and other expenses. Therefore, the price changes that indicate a specific type of construction sector should be estimated using suitable cost indices to achieve consistency in construction prices. In Jordan, many governmental institutions are involved in the reproduction of several types of Indicators. In this study, three main governmental indicators that have a direct effect on the construction industry had been chosen. In sequence, their ability to estimate the annual variations in the construction cost was measured. On the other hand, a new indicator had been constructed using the available material price lists. These indicators were also evaluated in terms of effectiveness to estimate the construction sector and then compared with others. The comparison of these indicators was based on efficiency to determine the prices of construction projects and their extent to impact the industry. In which the chosen indicators were effective in the estimation of both previous and current projects values and their ability to anticipate future prices. Finally, the most adequate cost indicator amongst them was considered to be applicable in the estimation process of the construction projects. Keywords: Cost index, Fluctuations, Regression Analysis, Future predictions, Construction cost, index, Inflation, Estimating, Forecasting.

ÖZ: İnşaat Maliyet Endeksi, inşaat sektörünü temsil eden belirli mal ve hizmetlerin zaman içindeki ortalama maliyet hareketinin bir göstergesidir. İnşaat fiyat göstergelerinin temel amacı, inşaat faaliyetinin girdilerinin veya çıktılarının fiyat değişikliklerinin derecesini tahmin etmektir. Bununla birlikte, kullanılan isimlendirme esas olarak endekslerin içeriğine bağlıdır ve ülkeler arasında değişebilir. Aynı zamanda, her bir bireysel inşaat projesi, yapısal elemanların, mekanik elemanların ve diğer masrafların belirli bir koleksiyonunun bir karışımıdır. Bu nedenle, belirli bir inşaat sektörünü gösteren fiyat değişiklikleri, inşaat fiyatlarında tutarlılığı sağlamak için uygun maliyet endeksleri kullanılarak tahmin edilmelidir. Ürdün'de birçok hükümet kurumu çeşitli Göstergelerin çoğaltılmasına katılmaktadır. Bu çalışmada, inşaat endüstrisi üzerinde doğrudan etkisi olan üç ana hükümet göstergesi seçilmiştir. Sırayla, inşaat maliyetindeki yıllık değişimleri tahmin etme yetenekleri ölçülmüştür. Öte yandan, mevcut malzeme fiyat listeleri kullanılarak yeni bir gösterge oluşturulmuştur. Bu göstergeler, inşaat sektörünü tahmin etmede etkinlik açısından da değerlendirilmiş ve daha sonra diğerleriyle karşılaştırılmıştır. Bu göstergelerin karşılaştırılması, inşaat projelerinin fiyatlarının belirlenmesinde verimliliğe ve bunların sanayiyi etkileme boyutuna dayanmaktadir ve seçilen göstergelerin hem önceki hem de mevcut proje değerleri ve gelecekteki fiyatları öngörme kabiliyetlerine etkilidir. Son olarak, aralarındaki en uygun maliyet göstergesinin inşaat projelerinin tahmin sürecinde uygulanabilir olduğu düşünülmüştür. Anahtar Kelimeler: Maliyet endeksi, Dalgalanmalar, Regresyon Analizi, Geleceğe
Master of Science in Civil Engineering. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2020. Supervisor: Assoc. Prof. Dr. Tolga Çelik.
Keywords: Civil Engineering; Construction industry--Building Costs--Cost Index--Jordan; Cost index; Fluctuations; Regression Analysis; Future predictions; Construction cost; index; Inflation; Estimating; Forecasting